Organizational Setup & Human Resource Profile of Handicraft Industry of District Saharanpur - Bansal, Ravi (Journal of Commerce and Trade, 2014)
Saharanpur is famous for its wood-carving industry. The Shivalik range provides the raw material for the industry. Woodwork of Saharanpur is exported to various countries like Germany, U.K., USA, Canada, Kuwait, Sweden, Singapore etc. Alike other handicraft industries, skilled craftsmanship are the principal feature of wood-carving industry of Saharanpur. On the other hand, a major part of wood-carving industry is in the hands of the middlemen. As a tradition, most of them carry their small-scale units and work on contract basis. They constitute a real link between the artisans, the exporters and the foreign buyers. Hence, the progress of wood-carving industry of Saharanpur primarily depends upon the craftsmanship of artisans along with professional skill of middlemen and exporters.